Research of opportunities for adaptation of computer-integrated mixture preparation systems to conditions of foundries in Ukrainian enterprises producing wear-resistant cast iron - Дымко, Егор Павлович; Высоцкий, Святослав Викторович; Красноухова, Анастасия Александровна; Николаева, Юлия Евгеньевна (Technology audit and production reserves, 2016)
The problems associated with the possibility of adaptation of modern computer-integrated control systems for control of imported mixture preparation equipment to the conditions of the foundries in Ukrainian enterprises are considered. It is emphasized that ensuring the given quality of a mixture is an important factor in determining the performance characteristics of wear-resistant cast iron castings. It is shown that the use of modern imported mixture preparation systems suggests the possibility of supplementing by models and algorithms of Ukrainian developments in the synthesis of molding compounds, and optimal control of mixture preparation processes. Proposed options that can complement the QualiMaster AT1/ SandReport/ SandExpert system are a variant of its adaptation to the conditions of foundries of the Ukrainian enterprises. These options are based on mathematical models «mixture composition – mixture properties» in the form of regression equations and algorithms for optimal control of mixture preparation sections. The use of these solutions provides the ability to improve performance, particularly durability of wear-resistant cast iron castings, working in conditions of intensive abrasive friction. This is due to the fact that factor in improving the durability is high quality of working surfaces formed at the «casting surface – molding sand» interface.